Bi-directional coupled tuned mass dampers for the seismic response control of two-way asymmetric-plan buildings. - Lin, Jui-Liang
This paper proposes bi-directional coupled tuned mass dampers (BiCTMDs) for the seismic response control of two-way asymmetric-plan buildings subjected to bi-directional ground motions. The proposed BiCTMD was developed from the three-degree-of-freedom modal system, which represents the vibration mode of a two-way asymmetric-plan building. The performance of the proposed BiCTMD for the seismic response control of elastic two-way asymmetric-plan buildings was verified by investigating the reductions of the amplitudes of the associated frequency response functions. In addition, the investigation showed that the proposed BiCTMD is effective in reducing the seismic damage of inelastic asymmetric-plan buildings. Therefore, the BiCTMD is an effective approach for the seismic response control of both elastic and inelastic two-way asymmetric-plan buildings.
Keywords: Tuned mass damper; Asymmetric-plan building; Vibration mode; Seismic response control